THE ROLE OF NURSES IN PREVENTING HOSPITAL-ACQUIRED INFECTIONS - Obaid Ali Alanazi, Mohammed Hleel Alharbi, Bander Misfer Mobarak Al Dawsary, Saeeda Hamed Albishi, Zahra Hassan Al Zaher, Fozeyah Abdurahman Alresheedi, Joza Dawi Alotibi, Anwar Suliman Alanazi, Mahmoud Shabib Al Dawsari, Khlefah Ganem Aldosari, ,; Bushra Othman Omar Alfoti, Manal Mohammad Salem Alanazi, Ahlam Abdullah Hakami, Moubark Obaid Saad Aldawsari, Sanaa Nasser Abuallah, Amal Khalf Alnomasi, Nasser Abrahim Al Doosari, (Chelonian Research Foundation, 2022)
The research investigating the connection between nurse staffing and hospital-acquired conditions is diverse due to the utilization of distinct terminology and methodologies. To conduct a comprehensive analysis and synthesis of original research investigating the correlation between nurse staffing levels and the occurrence of hospital-acquired conditions. This research was undertaken by a comprehensive analysis of relevant nursing literature using a systematic review approach. A systematic search was conducted in the CINAHL, Cochrane Library, DBpia, EBSCO, PubMed, PsycINFO, and RISS databases to identify papers published between January 2000 and August 2018 that investigated the relationship between nurse staffing and hospital-acquired conditions. Only articles written in English or Korean were included. Multiple metrics were used to investigate the correlation between nurse staffing and the occurrence of hospital-acquired conditions. Most of the studies that were analyzed showed that there is a negative correlation between the levels of nurse staffing and the occurrence of hospital-acquired conditions. Nevertheless, a considerable proportion of associations did not provide statistically significant results. Future research should focus on investigating the disparities in the correlation between nurse staffing and hospital-acquired conditions. It is crucial to employ accurate data collection methods to determine registered nurses' hours per patient day and total hours per patient day, as obtaining data on these measures is challenging. The results of this research indicate that having an adequate number of nurses on duty is a reliable measure of the delivery of high-quality patient care. Nevertheless, it is advisable to persistently pursue more research in order to establish more certain correlations between nurse staffing and hospital-acquired disorders, as well as to provide precise recommendations pertaining to nurse staffing techniques. Keywords: Nurse, hospital-acquired infection, review, nurse staffing.